Sistem Penunjang Keputusan Kenaikan Jabatan Pada PT. Metraplasa - Muhammad Hilman Fakhriza; Ispandi Ispandi (STMIK Budi Darma, 2018)
The purpose of this study is to help make employment decisions in PT. Metraplasa uses the best candidates from a number of existing employees, in this case the intended candidate is the employee entitled to occupy an available position based on the criteria specified. Analytical Hierarchy Process (AHP) is a method of decision making on the problem of determining the priority of choice from various alternatives. In the process of determining the hierarchical weighting factor as well as the evaluation factor, a consistency test should be performed (CR <.100). The application of AHP in this research is to determine the order of promotion factor. The result of this analysis is concluded that the factor of keniakan positions become discipline factor (36%), followed by responsibility factor (27%), cooperation factor (19%), and last is behavior factor (18%).